2021
DOI: 10.13189/ujaf.2021.090309
|View full text |Cite
|
Sign up to set email alerts
|

The Nexus between Innovation and Business Competitive Advantage: A Conceptual Study

Abstract: Despite the fierce competition in the business environment, firms accept relatively low innovative solutions in their daily activities and consequently lose competitive advantage, experience creeping growth at a snail's pace directly associated with the firm's inadequate finance and eventual collapse. This study examined the interrelationship between access to finance, innovation, and competitive advantage. Premised on the study findings, results revealed that innovation is an all-important strategy that diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 41 publications
(37 reference statements)
0
9
0
Order By: Relevance
“…There are many types of systematic review research, including bibliometric reviews that focus on the evolution of a scientific area over time [15][16][17][18][19][20][21][22][23], meta-analysis [24,25], systematic reviews [26][27][28][29][30][31][32], narrative reviews [33,34], framework-based reviews [35], and structured reviews, which focus on the widely applied theories, constructs, and methods [36].…”
Section: -Methodologymentioning
confidence: 99%
“…There are many types of systematic review research, including bibliometric reviews that focus on the evolution of a scientific area over time [15][16][17][18][19][20][21][22][23], meta-analysis [24,25], systematic reviews [26][27][28][29][30][31][32], narrative reviews [33,34], framework-based reviews [35], and structured reviews, which focus on the widely applied theories, constructs, and methods [36].…”
Section: -Methodologymentioning
confidence: 99%
“…The notion that innovation is a unique and strategic tool for pursuing performance or CA has persisted over time despite being controversial. Studies (Aziz & Samad, 2016;Boachie-Mensah & Acquah, 2015;Ferreira et al, 2018;Nafiu et al, 2020;Onileowo et al, 2021;Ukpabio et al, 2018) have been able to establish that there is a linear relationship between innovations and CA. There is a research oversight on the relevance of constructs and sub-constructs of innovations as exposed by Clauss (2016); as these have explanatory potential on the nature of the CA.…”
Section: Problem Statementmentioning
confidence: 99%
“…Izzati (2017), Wardani and Isabela (2017) and Widyasari, Harindahyani, and Rudiawarni (2017) support the finding that the strategy adopted by a company can influence earnings management actions. Onileowo, Muharam, Ramily, and Khatib (2021) showed that earnings management can be maintained by companies that develop innovation and maintain a competitive advantage.…”
Section: Theoretical Foundation and Development Hypothesismentioning
confidence: 99%